2024
DOI: 10.1038/s41588-023-01596-4
|View full text |Cite
|
Sign up to set email alerts
|

Multi-ancestry genome-wide association study of major depression aids locus discovery, fine mapping, gene prioritization and causal inference

Xiangrui Meng,
Georgina Navoly,
Olga Giannakopoulou
et al.

Abstract: Most genome-wide association studies (GWAS) of major depression (MD) have been conducted in samples of European ancestry. Here we report a multi-ancestry GWAS of MD, adding data from 21 cohorts with 88,316 MD cases and 902,757 controls to previously reported data. This analysis used a range of measures to define MD and included samples of African (36% of effective sample size), East Asian (26%) and South Asian (6%) ancestry and Hispanic/Latin American participants (32%). The multi-ancestry GWAS identified 53 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 88 publications
0
13
0
Order By: Relevance
“…Twenty-eight studies reported 98 estimates of the association between adiposity and depression 25,3235,37,40,4245,47,48,50,53,5559,6264,6670 , three studies reported 9 estimates for anxiety 25,41,67 , three studies reported 8 estimates for anorexia nervosa 61,67,68 , five studies reported 13 estimates for bipolar disorder 31,53,55,65,67 , three studies reported 7 estimates for OCD 61,67,68 , three studies reported 23 estimates for PTSD 49,60,67 , and twelve studies reported 26 estimates for schizophrenia 36,38,39,46,51,52,54,55,61,65,67,68 . One-sample MR design was conducted in six studies 33,34,43,56,57,62 , two-sample MR design was conducted in thirty-two studies 31,32,3542,4455,58,60,61,6369 , both one-sample MR and two-sample MR were conducted in three studies 25,59,70 . Thirty unique MR estimates out of 184 total estimates were included in meta-analyses (details as shown in “Yes” under “For meta-analysis” collum in Appendix).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-eight studies reported 98 estimates of the association between adiposity and depression 25,3235,37,40,4245,47,48,50,53,5559,6264,6670 , three studies reported 9 estimates for anxiety 25,41,67 , three studies reported 8 estimates for anorexia nervosa 61,67,68 , five studies reported 13 estimates for bipolar disorder 31,53,55,65,67 , three studies reported 7 estimates for OCD 61,67,68 , three studies reported 23 estimates for PTSD 49,60,67 , and twelve studies reported 26 estimates for schizophrenia 36,38,39,46,51,52,54,55,61,65,67,68 . One-sample MR design was conducted in six studies 33,34,43,56,57,62 , two-sample MR design was conducted in thirty-two studies 31,32,3542,4455,58,60,61,6369 , both one-sample MR and two-sample MR were conducted in three studies 25,59,70 . Thirty unique MR estimates out of 184 total estimates were included in meta-analyses (details as shown in “Yes” under “For meta-analysis” collum in Appendix).…”
Section: Resultsmentioning
confidence: 99%
“…We repeated the main analyses estimating the association of genetically predicted adiposity with depression including only studies that reported results with binary outcomes. In Appendix , nine studies with 15 estimates provided results with binary outcomes (OR 1.06, 95% CI 1.00-1.13) 33,50,57,58,63,64,67,69,70 . The findings were similar to the main analysis which included binary and continuous outcomes ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Genes significantly enriched for PTVs or damaging missense variants (p-value <0.01) in cases were subset from the summary statistics (https://bipex.broadinstitute.org). We obtained 450 major depression-associated genes from a GWAS analysis of 88,316 cases and 902,757 controls 23 . Schizophrenia-related genes were sourced from exome and GWAS analysis.…”
Section: Gene Set Enrichment Test For Neurological Disorders and Glio...mentioning
confidence: 99%
“… 84 Furthermore, genome-wide significant variants associated with the risk factors or symptomatic features of psychiatric disorders such as depression, SUDs, and PTSD are continually being identified, offering unprecedented insights for identifying novel therapeutic targets, repurposing existing drugs, and establishing target-based systems that also model relevant phenotype rescues. 85 , 86 , 87 Analyzing editing revertants in PSCs from donors with disease-linked variations allows for scrutinizing their genotype-phenotype relationship, whose functional implications are still unknown and could influence the clinical response to psychedelics.…”
Section: What Do Psc-derived Brain Cells Bring To Psychedelic Studies?mentioning
confidence: 99%